Nowcasting Jumlah Penumpang Udara di Kabupaten Berau Menggunakan Indeks Google Trends - Muhammad Rizki Yudistira (BESTARI BPS Kalimantan Timur, 2025)
Air transport holds a significant role in supporting the economic development of Berau Regency. Airports act as catalysts for economic growth and tourism development. Berau Regency is among the regions with high flight activity through one of the busiest airports in East Kalimantan. In 2023, the number of arriving passengers at Kalimarau Airport was 182,644. Moreover, Berau Regency is also one of the tourist destinations in East Kalimantan. Each year, the number of tourists visiting Berau Regency continues to increase. Every month, Statistics Indonesia of East Kalimantan releases data on air passengers in the region. However, there is a thirty-day delay after the end of the observed month, resulting in the absence of real-time data. To address this issue, a nowcasting model was developed using Google Trends index data. Modeling was conducted using the SARIMAX and Prophet models. After modeling and evaluation, it was found that the Prophet model with Google Trends index and holiday variables was the best-performing model. The nowcasting results for the number of air passengers in April and May were 16,247 and 14,766 passengers, respectively.